PENGARUH PEMANFAATAN PERPUSTAKAAN SEKOLAH TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SMAN 1 BANGKO BAGANSIAPIAPI - Elky Rahayu; Sumarno '; Henny Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research was conducted at SMAN 1 Bangko Bagansiapiapi Rokan Hilir Regency. The goal is to determine the effect of school library utilization on student achievement. The population in this research is 289 students and the sample is the students of class X and XI IPS of 74 students taken with Proportionate Random Sampling technique. Data collection technique is done through questionnaires and documentation techniques. Further data were analyzed using simple regression analysis. The results showed that the variable utilization of school libraries have an effect on student achievement variable with significance 0,001. To improve the learning achievement, students should improve the utilization of school libraries. For schools, to improve the use of school libraries need to add library materials such as reference books, enrichment books, journals, and textbooks so that learners can find a source of reference.Keywords: School Library Utilization, Learning Achievement